TREE SPECIES DIVERSITY AND ETHNOBOTANY OF DEGRADED PEAT SWAMP FOREST IN CENTRAL KALIMANTAN - Titi Kalima; Sri Suharti; Sumarhani Sumarhani; Liam A. Trethowan (Reinwardtia, 2020)
KALIMA, T., SUHARTI, S., SUMARHANI & TRETHOWAN, L. A. 2020. Tree species diversity and ethnobotany of degraded peat swamp forest in Central Kalimantan. Reinwardtia 19(1): 27‒54. ‒‒ Most peat swamp forest has been degraded. This has resulted in decline of its biodiversity. The objective of this study was to identify the composition, diversity, and plants used by local people in Bagantung swamp forest. The study was conducted on degraded peat swamp forest area in Bagantung, Mantangai Sub-District, Kapuas District, Central Kalimantan Province. The Shannon-Wiener (H’) and the Importance Value (IV) indices were used for analyzing the species diversity and the species importance across a number of forest plots. Useful tree species were identified by interviewing local villagers. There were 2,562 individual plants in 32 plots (each plot 20 m × 20 m). We identified 100 tree species and 16 non-tree species, from 74 genera, and 46 families. Myrtaceae, Sapotaceae, Ebenaceae, Dipterocarpaceae and Clusiaceae were the most dominant families. Large tree (H’=1.46) and small tree diversity was similar (H’=1.75). In both small and large tree size classes Calophyllum nodusum was the most dominant species. There were 16 tree species and two non-tree species used by local people for house and boat construction, furniture, handicrafts, medicine, and insect repellent.